Authentic Leadership and Employee Voice Behavior: A Multi-Level Psychological Process - Hsiung, Hsin-Hua (2012)
This study investigates the psychological process of how authentic leadership affects employee voice behaviors. The theoretical model of this study proposes that employee positive mood and leader–member exchange (LMX) quality mediate the relationship between authentic leadership and voice behavior, while the procedural justice climate moderates the mediation effects of positive mood and LMX quality. Multi-level data from 70 workgroups of a real estate agent company in Taiwan support all hypotheses. This study reveals the cross-level effects of authentic leadership, and provides practical suggestions to help employees express their opinions in organizations.
Keywords: Voice behavior; Procedural justice climate; Leader–member exchange; Positive mood; Authentic leadership